Semiotic Dimensions and Filmic Projections of African Socio-Cultural Realities in Selected Mount Zion Films - Falako, Francis O. (Ghana journal of religion and theology, 2024)
This paper discusses audience perceptions of how two Mount Zion films (The Gods Are Dead, and Land of Fury) project African culture. Also, it probes into the implications of the attitude of Evangelical films to African cultural practices. The study is a case-oriented qualitative comparative analysis; it adopts an ethnographic method to elicit data using a structured questionnaire, in-depth interviews with Key Informants (KII), and Focused Group Discussions (FGD) methods. Between October 2021 and March 2022, the researcher screened the two videos to purposively selected audiences in Lagos, Enugu, and Abuja. Findings reveal convergences and areas of divergences between African and Biblical worldviews, distortions, and a negative portrayal of African realities. The study recommends an emphatic appreciation of African culture and further analytical studies toward identifying the trends and twists in producing evangelical videos.